Radiographic abnormalities among Finnish construction, shipyard and asbestos industry workers - Koskinen, Kai; Zitting, Antti; Tossavainen, Antti; Rinne, J.-P.; Roto, Pekka; Kivekäs, J.; Reijula, Kari; Huuskonen, Matti S. (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The prevalence of asbestos-related radiographic abnormalities was surveyed among Finnish construction, shipyard, and asbestos industry workers.Methods The radiographic screening focused on active and retired workers who were under the age of 70 years and had been employed for at least 10 years in construction or for at least 1 year in shipyards or in the asbestos industry. In 1990--1992, 18 943 people participated in an X-ray examination of the lungs and an interview on work history and exposure. The criteria for a positive radiological finding were (i) small irregular lung opacities clearly consistent with interstitial pulmonary fibrosis (ILO 1/1 or higher), (ii) lung opacities indicating mild pulmonary fibrosis (ILO 1/0) with unilateral or bilateral pleural plaques, (iii) marked adhesions with or without thickening of the visceral pleura, or (iv) findings consistent with bilateral pleural plaques. Results Fulfilling the criteria were 4133 workers (22%) (22% from construction, 16% from shipyards, and 24% from the asbestos industry). The radiological findings included signs of pulmonary fibrosis (3%), changes in the visceral pleura (7%), bilateral plaques (17%), and unilateral plaques (10%). Occupational disease was diagnosed according to the Finnish insurance regulations for three-fourths of those referred for further examinations, 96% being abnormalities in the pleura and 4% being asbestosis.' ' CONCLUSION ': 'Exposure to asbestos dust has been common in ordinary construction work, and, consequently, radiographic abnormalities (mostly pleural) occur frequently among active and retired workers.
Keywords: anthophyllite; asbestosis; chrysotile; fibrosis; pleural abnormality; screening